Heuristics as decision rules: Part I: the single consumer - Werner Güth; Wilhelm Neuefeind (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
Many consumption prices are highly volatile. It would certainly overburden our cognitive system to fully adjust to all these changes. Households therefore often rely on simple heuristics when deciding what to consume, e.g. in the form of a constant budget share for a specific consumption commodity, like a vacation, or of a constant consumption amount for lowcost commodities as food items. Using utility functions we can measure the welfare loss, caused by such heuristics, and to what extent this can be reduced by adaptation. In the present Part I the analysis is mainly restricted to a single consumer with a Cobb-Douglas utility function. General utility functions will also be considered. Part II will study exchange economies.
urn:nbn:de:kobv:11-10048737
Keywords: 330